Redistribution of pyrogenic carbon from hillslopes to stream corridors following a large montane wildfire. Issue 9 (24th September 2016) - Cotrufo, M. Francesca; Boot, Claudia M.; Kampf, Stephanie; Nelson, Peter A.; Brogan, Daniel J.; Covino, Tim; Haddix, Michelle L.; MacDonald, Lee H.; Rathburn, Sarah; Ryan‐Bukett, Sandra; Schmeer, Sarah; Hall, Ed
Abstract: Pyrogenic carbon (PyC) constitutes a significant fraction of organic carbon in most soils. However, PyC soil stocks are generally smaller than what is expected from estimates of PyC produced from fire and decomposition losses, implying that other processes cause PyC loss from soils. Surface erosion has been previously suggested as one such process. To address this, following a large wildfire in the Rocky Mountains (CO, USA), we tracked PyC from the litter layer and soil, through eroded, suspended, and dissolved solids to alluvial deposits along riversides. We separated deposited sediment into high‐ and low‐density fractions to identify preferential forms of PyC transport and quantified PyC in all samples and density fractions using benzene polycarboxylic acid markers. A few months after the fire, PyC had yet to move vertically into the mineral soil and remained in the organic layer or had been transported off site by rainfall driven overland flow. During major storm events PyC was associated with suspended sediments in river water and later identified in low‐density riverbank deposits. Flows from an unusually long‐duration and high magnitude rainstorm either removed or buried the riverbank sediments approximately 1 year after their deposition. We conclude that PyC redistributes after wildfire in patterns that are consistent with erosion and deposition of low‐density sediments. A more complete understanding of PyC dynamics requires attention to the interaction of post fire precipitation patterns and geomorphological features that control surface erosion and deposition throughout the watershed. Key Points: Surface erosion is a major loss pathway of PyC from burned mountain soils PyC is transported primarily with the low‐density organic fraction of sediments PyC can accumulate for millennia in alluvial deposits of burned watersheds